Persistence of immunity following a booster dose of Haemophilus influenzae type B-Meningococcal serogroup C glycoconjugate vaccine: follow-up of a randomized controlled trial. - Khatami, A; Snape, MD; John, T; Westcar, S; Klinger, C; Rollinson, L; Boutriau, D; Mesaros, N; Wysocki, J; Galaj, A; Yu, L; Pollard, A (2011)
BACKGROUND: Antibodies against Haemophilus influenzae type b (Hib) and serogroup C Neisseria meningitidis (MenC) wane after early infant immunization. METHODS: Children previously immunized in a randomized controlled trial at ages 2, 3, and 4 months with DTPa-IPV-Hib and MenC-CRM197 (MenC-CRM group) or DTPa-IPV and Hib-MenC-TT (Hib-MenC-TT group) had blood samples drawn at 1 and 2 years following a booster dose of Hib-MenC-TT at 12 to 15 months of age. A blood sample was also drawn at the year 2 follow-up from a separately recruited age-matched control group who had not received a booster. RESULTS: In 271 children at year 1, mean 14.6 months (range: 12-18 months) following the Hib-MenC-TT booster, MenC bactericidal titers above the protective threshold (rSBA ≥ 1:8) was demonstrated in 89.0% of the Hib-MenC-TT group and 69.5% of MenC-CRM participants. Antipolyribosylribitol phosphate Ig ≥ 1.0 μg/mL (Hib correlate for long-term protection) was seen in 94.9% and 82.5%, respectively.In 379 participants (including 72 control children) at year 2 (age: 39-43 months, 25-31 months post Hib-MenC-TT) persistence of MenC antibodies was demonstrated in 67.1% of the Hib-MenC-TT group and 40.5% of the MenC-CRM group, compared with 44.1% of control group participants. Antipolyribosylribitol phosphate Ig ≥ 1.0 μg/mL was seen in 89.0%, 74.7%, and 38.9%, respectively. CONCLUSIONS: A toddler Hib-MenC-TT booster helps sustain immunity against Hib to 3½ years of age. Persistence of MenC antibody is similar in children primed with MenC-CRM197 in infancy who receive a booster Hib-MenC-TT, to those who receive no booster. Persistence of MenC antibody is better when primed and boosted with Hib-MenC-TT.